Budget Supervision and Mechanism by an Administrative Village in Indonesia - Roy Marthen Moonti; Ibrahim Ahmad (Sriwijaya Law Review, 2019)
The role of government in budget management is something that must be done adequately based on the principles such as transparency, accountability, participation, and aspiration; because it is closely related to services in the village. The budget management should be conducted based on the applicable regulations. However, there are often found many village apparatus who has a potency to abuse their power in its authorities. This phenomenon, furthermore, causing some polemics among peoples and tends to abandon some regulations which should become a basis of the apparatus policies. The research aims at investigating the mechanism of village development budget management and the control of village development budget management. The mechanism, however, should be started with proper planning, budgeting, implementation, business manager, report, and accountability. Also, management control is must be done through several stages, such as pre supervision, channelization, use, and post channelization.